Definitive Simultaneous Integrated Boost Versus Conventional-Fractionated Intensity Modulated Radiotherapy for Patients With Advanced Esophageal Squamous Cell Carcinoma: A Propensity Score-Matched Analysis - Li, Chen; Tan, Lijun; Liu, Xiao; Wang, Xin; Zhou, Zongmei; Chen, Dongfu; Feng, Qinfu; Liang, Jun; Lv, Jima; Wang, Xiaozhen; Bi, Nan; Deng, Lei; et al. (Frontiers in Oncology, 2021)
Abstract Background The aim of this study was to compare the effects of simultaneous integrated boost–intensity modulated radiotherapy (SIB-IMRT) and conventional fractionated-IMRT (CF-IMRT) in definitive radiotherapy of esophageal squamous cell carcinoma (ESCC). Methods The data of 1173 patients treated with either CF-IMRT or SIB-IMRT for a curative intent from 2005 to 2016 were retrospectively reviewed. Propensity score matching (PSM) was used to create a well-balanced cohort of 687 patients at 1:2 ratio (237 patients in SIB-IMRT group and 450 patients in CF-IMRT group). Overall survival (OS), progression-free survival (PFS), recurrence pattern, and toxicity profiles were evaluated and compared between the two groups after PSM. Results After a median follow-up time of 42.3 months (range, 3.0-153.2 months) for surviving patients, survival results were comparable in the two groups. After PSM, the 1-year, 2-year and 4-year OS rates in the SIB-IMRT and CF-IMRT groups were 70.0% vs. 66.4%, 41.9% vs. 41.7% and 30.2% vs. 27.6%, respectively (p = 0.87). The 1-year, 2-year and 4-year PFS rates were 48.4% vs. 49.1%, 31.2% vs. 29.4%, and 26.1% vs. 17.9%, respectively (p = 0.64). Locoregional recurrence (p = 0.32) and distant metastasis (p = 0.54) rates were also comparable between two groups. The toxicity profile was similar in the two groups. Multivariate analyses in the matched samples showed that female, concurrent chemotherapy and earlier clinical stage were independently associated with longer OS and PFS. Conclusions SIB-IMRT appears to be equivalent to CF-IMRT in treatment efficacy and safety, and could become an alternative option for definitive radiotherapy of ESCC.